Nurse Continuity and Hospital-Acquired Pressure Ulcers: A Comparative Analysis Using an Electronic Health Record "Big Data" Set. Issue 5 (September 2015) - Stifter, Janet; Yao, Yingwei; Lodhi, Muhammad Kamran; Lopez, Karen Dunn; Khokhar, Ashfaq; Wilkie, Diana J.; Keenan, Gail M.
Abstract : Background: Little research demonstrating the association between nurse continuity and patient outcomes exists despite an intuitive belief that continuity makes a difference in care outcomes. Objective: The aim of this study was to examine the association of nurse continuity with the prevention of hospital-acquired pressure ulcers (HAPU). Methods: A secondary use of data from the Hands on Automated Nursing Data System (HANDS) was performed for this comparative study. The HANDS is a nursing plan of care data set containing 42, 403 episodes documented by 787 nurses, on nine units, in four hospitals and includes nurse staffing and patient characteristics. The HANDS data set resides in a "big data" relational database consisting of 89 tables and 747 columns of data. Via data mining, we created an analytic data set of 840 care episodes, 210 with and 630 without HAPUs, matched by nursing unit, patient age, and patient characteristics. Logistic regression analysis determined the association of nurse continuity and additional nurse-staffing variables on HAPU occurrence. Results: Poor nurse continuity (unit mean continuity index = .21–.42 [1.0 = optimal continuity]) was noted on all nine study units. Nutrition, mobility, perfusion, hydration, and skin problems on admission, as well as patient age, were associated with HAPUs ( p < .001). Controlling for patient characteristics, nurse continuity, and the interactions between nurse continuity and other nurse-staffing variables were not significantly associated with HAPU development. Discussion: Patient characteristics including nutrition, mobility, and perfusion were associated with HAPUs, but nurse continuity was not. We demonstrated a high level of variation in the degree of continuity between patient episodes in the HANDS data, showing that it offers rich potential for future study of nurse continuity and its effect on patient outcomes.